Hydrothermal Synthesis of TiO2 Hollow Nanospheres via Self-Assembly Process - Yang, Hai-Jian; Shen, Kai; Yang, Qi-Hao; Hu, Jin-Lin; Qian, Hai-Sheng (Asian Journal of Chemistry, 2013)
One-step self-assembly process was proposed to synthesize anatase TiO2 hollow nanospheres from octadecyltrimethoxysilane and tetrabutyl titanate at 120 ºC. The as-prepared product was characterized by X-ray diffraction, field-emission scanning electron microscopy and transmission electron microscopy, respectively. The morphology and size of the as-prepared sample can be adjusted by varying the temperature and the amount of octadecyltrimethoxysilane. Octadecyltrimethoxysilane plays a key role in the formation of hollow nanospheres of anatase TiO2. In particular, the as-synthesized TiO2 hollow nanospheres will be of great importance due to their potential applications in photocatalysis, drug delivery, separations and cell targeting, etc.